Implementasi Model Pembelajaran Project Based Learning Terintegrasi Praktikum Studi Antagonisme Escherichia coli dan Candida albicans Terhadap Keterampilan Berpikir Kritis Mahasiswa - Nur Istiqomah*; Noor Hujjatusnaini; Nurul Septiana; Astuti Muh. Amin (Universitas Syiah Kuala, 2022)
Critical thingking skills are high level thingking habits that will give rise to intelligent characters so that they can face various problems. Learning that is often directed at memorization and remembering results in students’ critical thingking skills being difficult to develop. This research aims to improve students’ critical thingking skills after the implementation the project based learning model integrated practicum. The type of research used is quasi experimental using a non-equivalent control group design. Data collection techniques obtained from test questions and observation sheets. The data analysis techniques used are the statistical of the t test and the N-gain test. The results showed that the implementation of the project based learning integrated practicum model was effective in the high level class group in the experimental class with an N-gain score (%) of 70,35. This is supported by the results of the paired sample t test with a significant value 0. The effect of the implementation of the project based learning integrated practicum model on students critical thingking skills based on the independent t test, namely in the experimental class got a result of 74,5 and in the control class got a result of 61,84. It can be concluded that the implementation of the project based learning integrated practicum model affects students’ critical thingking skills. Finding that became main target in this research was learning model which integrated with pratical work activity that able to improve critical thingking skill